User Pairing and Beamforming Design in mmWave CR-NOMA Networks - Akyol, Omer Faruk; Basaran, Semiha Tedik; Hokelek, Ibrahim; Gorcin, Ali (IEEE, 2023)
This paper presents the coexistence of two promising technologies for 5G and beyond mobile networks, namely Cognitive Radio-based Non-Orthogonal Multiple Access (CR-NOMA) and millimeter-wave (mmWave) wireless communication. The decoding performance of successive interference cancellation (SIC) significantly affects the coverage probability of the CR-NOMA network serving the primary and secondary users within a single frequency resource block. In this paper, we propose a user pairing algorithm to allocate primary and secondary users in an uplink mmWave CR-NOMA network, where the multi-antenna base station utilizes beamforming technology. The coverage probability is aimed to be maximized by selecting a secondary user in such a way that the Quality of service (QoS) requirements of both users are satisfied using the QoS-based SIC; otherwise, the channel state information-based SIC is utilized by selecting the secondary user with the best channel condition. We conduct Monte Carlo simulation experiments by varying the transmit power of the users, the number of antenna elements at the base station, and the number of secondary users in the network. The numerical results demonstrate that the proposed algorithm provides the optimum coverage probability with lower complexity, especially in higher signal-to-noise ratio regimes.
Keywords: cognitive radio; successive interference cancellation; coverage probability; non-orthogonal multiple access; beamforming; millimeter wave; OF-THE-ART; Computer Science; Telecommunications